Counting Down : A Memoir of Foster Parenting and Beyond - Gold, Deborah (Pseudonym); M., Michael (Pseudonym) (Book collections on Project MUSE., 2018)
"When Deborah Gold and her husband signed up to foster parent in their rural mountain community, they did not foresee that it would lead to a rollercoaster fifteen years of involvement with the traumatized yet resilient birth family. They fell in love with Michael (a toddler when he came to them), yet they had to reckon with the knowledge that he could leave their lives at any time. In Counting Down, Gold artfully tells her story of forging a family within an often-confounding system, in ways that defied the expectations of everyone involved. The remarkable characters we meet include social workers, a birth mother with the courage to give her children the childhood she never had herself, and a father parenting from prison. We also encounter members of a remarkable fellowship of Appalachian foster parents--gay, straight, right, left, evangelical, and atheist--united by love, loss, and quality hand-me-downs. Unlike child welfare manuals and textbooks, Gold's memoir brings us a foster parent's perspective (and, through Michael's own poetry and essays, that of a former foster child). The book shakes up common assumptions, and offers a hopeful look at an experience usually portrayed as bleak. For those who have fostered, Counting Down will be validating and familiar; for everyone else, it will inspire."--Amazon.com.